2009
DOI: 10.1091/mbc.e09-01-0085
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Inhibits ATR Signaling to Cell Cycle Checkpoints and DNA Repair

Abstract: DNA damage activates the ataxia telangiectasia-mutated and Rad3-related (ATR) kinase signal cascade. How this system is restrained is not understood. We find that in estrogen receptor (ER)-positive breast cancer cells, UV or ionizing radiation and hydroxyurea rapidly activate ATR-dependent phosphorylation of endogenous p53 and Chk1. 17-beta-estradiol (E(2)) substantially blocks ATR activity via plasma membrane-localized ERalpha. E(2)/ER reduces the enhanced association of ATR andTopBP1 proteins that follows DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 54 publications
1
68
0
Order By: Relevance
“…Inhibition of normal DNA repair signaling may simulate genetically based loss of DNA damage response signaling molecules such as ataxia telangiectasia mutated (ATM), ataxia telangiectasia and rad3-related protein (ATR), DNAdependent protein kinase (DNAPK), breast cancer 1 (BRCA1) and BRCA 2, p53, and Chk2 that predispose normal cells to acquire transforming mutations [79]. A recent report showed that in ER-positive breast cancer cells, DNA damaging agents including Uv, ionizing radiation, and hydroxyurea rapidly activated ATR-dependent phosphorylation of endogenous p53 and Chk1 [80]. The pathway involves extranuclear actions by E2 via plasma membrane-localized ERα and the activation of PI3K/Akt signaling pathway.…”
Section: E2 Signaling In Breast Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of normal DNA repair signaling may simulate genetically based loss of DNA damage response signaling molecules such as ataxia telangiectasia mutated (ATM), ataxia telangiectasia and rad3-related protein (ATR), DNAdependent protein kinase (DNAPK), breast cancer 1 (BRCA1) and BRCA 2, p53, and Chk2 that predispose normal cells to acquire transforming mutations [79]. A recent report showed that in ER-positive breast cancer cells, DNA damaging agents including Uv, ionizing radiation, and hydroxyurea rapidly activated ATR-dependent phosphorylation of endogenous p53 and Chk1 [80]. The pathway involves extranuclear actions by E2 via plasma membrane-localized ERα and the activation of PI3K/Akt signaling pathway.…”
Section: E2 Signaling In Breast Carcinogenesismentioning
confidence: 99%
“…Ligand-bound ERα regulates ATR activity by potentiating the Akt-mediated phosphorylation of DNA topoisomerase 2-binding protein 1 (TOPBP1) at serine 1159, which prevents the binding of TOPBP1 with ATR after DNA damage. Since the association of Chk1 with claspin is important for Chk1 activity, E2-ERα regulates Chk1 activity via Akt-mediated phosphorylation of Chk1, which prevents its association with claspin and the signal transduction to the G2/M checkpoint [80]. ATM protein expression is found to be aberrantly reduced more frequently among BRCA1-and BRCA2 mutation carrier tumors than in non-BRCA1/2 mutation carrier tumors, therefore reduced ATM expression was found more often in ER-and PR-negative breast cancer indicating loss-of-function interaction among these molecules [81].…”
Section: E2 Signaling In Breast Carcinogenesismentioning
confidence: 99%
“…Furthermore, estrogen metabolism produces genotoxic by-products that can directly damage DNA, 9 thereby disrupting normal cellular processes such as apoptosis, proliferation and DNA repair. 1,[10][11][12] As a strong promoting agent, estrogen-driven proliferation not only increases the number of estrogen-responsive cells but also potentially stimulates clonal expansion of pre-cancerous cells. [13][14][15] Interestingly, the promotion of these initiated cells requires continuous exposure to estrogen to progress preneoplastic lesions to a state of transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen has been shown to inhibit ATR activation through phosphatidylinositol 3-kinase (PI3K)/Akt action, which inhibits the interaction between ATR and wild-type TopBP1 but not S1159A mutant TopBP1 (21). Estrogen also inhibits the interaction between Chk1 and claspin via phosphorylation of Chk1 by Akt (21).…”
mentioning
confidence: 99%
“…Estrogen also inhibits the interaction between Chk1 and claspin via phosphorylation of Chk1 by Akt (21). Therefore, the underlying mechanism by which Akt inhibits the checkpoint response may involve multiple regulators.…”
mentioning
confidence: 99%